wâhkôtowin: A nehiyaw Ethical Analysis of Anti-Indigenous Racism in Canadian Nursing - Meghan Eaker (York University Libraries, 2021)
Indigenous peoples in the settler state of Canada face racism on a daily basis, including in their interactions with nurses and the healthcare system. Canadian Nursing consistently fails to recognize their role in continuing to perpetrate anti-Indigenous racism. Many nurses are not taught enough about Indigenous history, settler colonialism and anti-racism to be able to recognize anti-Indigenous racism in practice, let alone effectively address it. Often the western based ethical principles nurses are taught in schools are weaponized against Indigenous peoples in practice. I propose using the nehiyaw (Cree) concept of wâhkôtowin as an ethical perspective that can help nurses tackle the problem of anti-Indigenous racism.